Pengaruh Kualitas Pelayanan dan Kinerja Pegawai terhadap Kepuasan Masyarakat - Sukmarini, Ni Luh Putu Dian; Kawiana, I Gede Putu; Pratiwi, Komang Ary (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The formulation of the problem and the purpose of this study is to determine the partial and simultaneous influence of service quality and employee performance on community satisfaction. This research was conducted at the Kerambitan Village Office of Tabanan Regency. The number of samples in this study was 96 respondents, with non-probability sampling methods, especially purposive sampling. Data collection was carried out through observation, interviews and questionnaires. The analysis technique used is multiple linear regression. The results of the analysis show that partially the variables of Service Quality and Employee Performance have a positive and significant effect on Community Satisfaction and the simultaneous influence of the variables of Service Quality and Employee Performance on Community Satisfaction at the Kerambitan Village Office. This is evidenced by the value of Fhitung = 164.616 greater than the value of Ftabel = 3.09. The value of the coefficient of determination was obtained 78% while the remaining 22% was influenced by other factors that were not studied in this study. So it can be concluded that the Quality of Service and Employee Performance simultaneously have a positive and significant effect on Community Satisfaction at the Kerambitan Village Office. It is recommended to the Kerambitan Village Office to further improve higher quality services and balanced with good employee performance, so that service users feel more satisfied in using public services, especially at the Kerambitan Village Office.